Estudo da metilação em genes de reparo, mutação no gene BRAF e instabilidade de microssatélites em indivíduos com Câncer Colorretal - Carla Gomes Rasuck (2011)
Colorectal Cancer (CRC) corresponds to the third most prevalent type of cancer. Its origins can either be sporadic or inherited, being Lynch Syndrome the most common form of hereditary CRC. The activation of BRAF oncogene, inactivation of mismatch repair genes by methylation of CpG islands, and microsatellite instability (MSI) have been reported to be involved in CRC development. The goal of the study was to characterize CRC tumors using clinical and molecular criteria through association and cluster analysis. Amsterdam II and Bethesda guidelines and molecular variables were analyzed in 77 patients from Brazil. The positive replication error (RER) status, based in microsatellite instability, showed association with metachronous tumor, MLH1 gene methylation and inverse association with left sided and synchronous tumors. The PMS2 gene was considered the best predictor for differentiating levels of methylation and the mononucleotide were considered the best markers to evaluate RER status. The cluster 1 was characterized of individuals over 60 years of age, female, right-sided tumor, high microsatellite instability, and metachronous or synchronous tumors. The individuals in cluster 2 were younger than 45 years of age, male and showed left-sided or rectum tumors, and microsatellite stability. Even though it was not observed a significant association, a higher number of individuals with family history of cancer and tumors without promoter methylation were found in cluster 2. The V600E mutation did not show association with clinical or molecular characteristics. Evaluation of MSI and methylation of MLH1 and PMS2 genes should be considered in order to assist with clinical diagnosis.